2008
DOI: 10.1016/j.ejpain.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen‐enhanced spinal cord stimulation and intrathecal baclofen alone for neuropathic pain: Long‐term outcome of a pilot study

Abstract: In a previously published pilot study, we addressed the possibility to increase the effectiveness of spinal cord stimulation (SCS) applied for neuropathic pain by using adjunct pharmacological therapy. This combined treatment approach was a direct spin-off from animal experiments aiming at the exploration of transmitter and receptor mechanisms involved in the pain relieving effect of SCS. Out of 48 patients with neuropathic pain of peripheral origin responding poorly to SCS, seven received pumps for intratheca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 12 publications
3
53
0
4
Order By: Relevance
“…Lind et al illustrated the administration of intrathecal baclofen in patients increasing the effects of SCS in neuropathic pain of peripheral origin. These patients initially responded poorly to SCS however they experienced a satisfactory relief during SCS (Lind et al, 2004, Lind et al, 2008. A promising observation was that follow-up obviously demonstrated a sustained pain relieving effect.…”
Section: Neurochemistrymentioning
confidence: 82%
“…Lind et al illustrated the administration of intrathecal baclofen in patients increasing the effects of SCS in neuropathic pain of peripheral origin. These patients initially responded poorly to SCS however they experienced a satisfactory relief during SCS (Lind et al, 2004, Lind et al, 2008. A promising observation was that follow-up obviously demonstrated a sustained pain relieving effect.…”
Section: Neurochemistrymentioning
confidence: 82%
“…Basic research has revealed the role of GABA-B receptors in the central nervous system in the regulation of pain [16]. Some clinical studies have also demonstrated the analgesic effect of ITB in treating intractable pain syndromes after spinal cord injury or cerebral infarction [13,14,15]. ITB may reduce neuropathic pain by modulating spinal GABA mechanisms, and thus, ITB can be an important option for patients with CRPS whose conditions are refractory to other methods of pain control [11,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, intrathecal baclofen (ITB) therapy alone did not appear to be sufficient for providing dramatic pain relief in patients with CRPS. Recently, some reports have suggested that ITB therapy can enhance the effect of SCS [11,12,13]. Furthermore, ITB therapy has been reported to be an effective modality for treating fixed dystonia related to CRPS [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…After an average follow-up of 6 years, they continued to enjoy >50 % improvement in pain scores. Although the dose of baclofen had to be gradually increased over the years, the range of daily doses was 140-270 μg at the last follow-up [39].…”
Section: Addition Of Neurochemicalsmentioning
confidence: 99%
“…Intrathecal adenosine turned out to be "technically problematic" [38], but intrathecal baclofen, the GABA-B receptor agonist that is commonly used both orally and intrathecally for the treatment of spasticity, has been evaluated in a prospective fashion [38,39]. Out of 48 patients who received an intrathecal baclofen bolus during SCS trial, 20 obtained a pain relief reduction of >50 %; of these, 7 were implanted with an intrathecal baclofen pump and SCS system [39]. After an average follow-up of 6 years, they continued to enjoy >50 % improvement in pain scores.…”
Section: Addition Of Neurochemicalsmentioning
confidence: 99%